Leitura e Desleitura na obra de Lygia Bojunga - Palhano, Tatiana Coelho (2009)
The purpose of this work is to know the reader behind the writer Lygia Bojunga Nunes. Observing her not only as a sender of a text, but as its recipient; revealing, therefore, how she connects, as a reader, with the literary work. This research is divided into three chapters. In the first chapter we try to connect the writer with the social, historical and political context where she had her origins, as well as the conditions which she developed her work in, from the early 1970s until the present moment. In the second chapter we analyze, in light of the influences of the literary tradition, her impressions of works, authors, characters; and the reaction that she had to certain readings. In the last chapter we have the study of the resources which Lygia Bojunga makes use in the linguistic system to give her creation esthetic value, bringing a rich and expressive subjectivity out; revealing, therefore, the unmistakable Lygia Bojunga‘s way of writing. To develop this work, we searched for theoretical basis in authors like: Nicolau Sevcenko (2001), Gilberto de Mello Kujawski (1991), Harold Bloom (1995), Pierre Bourdieu (1996), Dominique Maingueneau (2001) e Roland Barthes (1986). This theoretical basis was developed in a historical, formal and comparative based methodology. Therefore, the justification of the propositions in this research is given through examples extracted from Lygia Bojunga Nunes‘ works, twenty-one published works altogether